Answer:
Explanation:
The formula for determining the nth term of an arithmetic sequence is expressed as
f(n) = a + d(n - 1)
Where
a represents the first term of the sequence.
d represents the common difference.
n represents the number of terms in the sequence.
From the information given,
a = 13
d = 24 - 13 = 11
14) Therefore, the explicit formula for the arithmetic sequence is
f(n) = 13 + 11(n - 1)
15) when n = 40,
f(n) = 13 + 11(40 - 1)
f(n) = 13 + 429
f(n) = 442
16) if f(n) = 299,
299 = 13 + 11(n - 1)
11(n - 1) = 299 - 13
11(n - 1) = 286
Dividing through by 11, it becomes
n - 1 = 286/11 = 26
n = 26 + 1
n = 27